2009
DOI: 10.2169/internalmedicine.48.1616
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inflammatory Demyelinating Polyneuropathy after Treatment with Interferon-.ALPHA.

Abstract: Interferon-α (IFN-α)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
0
11
0
2
Order By: Relevance
“…On the other hand, autoimmunity is a well-recognized complication of IFNα therapy, with reported frequencies ranging between 4.3% and 18.5% in large observational studies (3)(4)(5). Neuropathies due to administration of IFNα are a rare complication (3,4); however, eight distinct case reports have shown that chronic inflammatory demyelinating polyneuropathy (CIDP) can result from administration of IFNα, presumably due to perturbations in the host immune system (6)(7)(8)(9)(10)(11)(12)(13). We here report a biopsy-proven case with IFNα-induced CIDP in which the serum value of tumor necrosis factor-α (TNFα) was elevated.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, autoimmunity is a well-recognized complication of IFNα therapy, with reported frequencies ranging between 4.3% and 18.5% in large observational studies (3)(4)(5). Neuropathies due to administration of IFNα are a rare complication (3,4); however, eight distinct case reports have shown that chronic inflammatory demyelinating polyneuropathy (CIDP) can result from administration of IFNα, presumably due to perturbations in the host immune system (6)(7)(8)(9)(10)(11)(12)(13). We here report a biopsy-proven case with IFNα-induced CIDP in which the serum value of tumor necrosis factor-α (TNFα) was elevated.…”
Section: Introductionmentioning
confidence: 99%
“…GBS associated with peginterferon alfa2a for CHC [6][7][8][9]11] . We did not test for IFN antibodies (that could possibly cross-react), did not rule out all the GBS related infectious causes definitely and did not check autoimmune markers at the time of onset of neurological symptoms.…”
Section: Treatmentmentioning
confidence: 99%
“…Significant neurological side effects such as nerve palsy and peripheral neuropathy are rare [6] . A few cases of Bell' s Palsy and chronic inflammatory demyelinating po-lyneuropathy (CIDP) and even one case of acute demyelinating polyneuropathy (AIDP) with atypical features for Guillain-Barre syndrome (GBS) associated with Interferon therapy have been reported, but no report of GBS with typical features has been published [5][6][7][8][9] . We present a case report of GBS that developed at wk 8 of therapy with Peginterferon alfa-2a.…”
Section: Introductionmentioning
confidence: 99%
“…A polineuropatia desmielinizante inflamatória crônica associa-se muitas vezes com doenças virais, como vírus da imunodeficiência humana (HIV) e o vírus da hepatite C (HCV) 1 . Muito recentemente, não apenas o agente viral, mas também o tratamento com imunomoduladores, como o interferon peguilado alfa (INFα), tem sido correlacionado com surgimento de PDIC 2,3 . Este relato de caso refere-se a um paciente imunodeprimido com síndrome da imunodeficiência adquirida (SIDA) e HCV que evoluiu com PIDC secundária ao uso de INFα2b, com excelente resposta à terapia com imunoglobulina humana hiperimune (IHH).…”
Section: Relato Do Casounclassified
“…Apesar de ser uma reação adversa pouco comum, outros casos na literatura vem demonstrando essa associação 2,3,7,10 , e o fato da estavudina poder ter concorrido para este quadro representa mais um alerta aos médicos que tratam pacientes co-infectados HIV/HCV, para as possíveis toxicidades concomitantes das medicações usadas.…”
Section: Relato Do Casounclassified